Antifungal and Antibiofilm Efficacy of Paeonol Treatment Against Biofilms Comprising Candida albicans and/or Cryptococcus neoformans - Qian, Weidong; Li, Xinchen; Liu, Qiming; Lu, Jiaxing; Wang, Ting; Zhang, Qian (Frontiers in Cellular and Infection Microbiology, 2022)
Fungal populations are commonly found in natural environments and present enormous health care challenges, due to increased resistance to antifungal agents. Paeonol exhibits antifungal activities; nevertheless, the antifungal and antibiofilm activities of paeonol against Candida albicans and Cryptococcus neoformans remain largely unexplored. Here, we aimed to evaluate the antifungal and antibiofilm activities of paeonol against C. albicans and/or C. neoformans (i.e., against mono- or dual-species). The minimum inhibitory concentrations (MICs) of paeonol for mono-species comprising C. albicans or C. neoformans were 250 μg mL-1, whereas the MIC values of paeonol for dual-species were 500 μg mL-1. Paeonol disrupted the cell membrane integrity and enhanced the influx of antibiotics into cells of mono- and dual-species, suggesting its antifungal mode of action. Moreover, mono- and dual-species cells within C. albicans and C. neoformans biofilms were damaged by paeonol at 8 times the MIC, as were effective against their planktic cells. In particular, at 4 and 8 mg mL-1, paeonol efficiently dispersed preformed 48-h biofilms formed by mono- and dual-species, respectively. Paeonol inhibited effectively the yeast-to-hyphal-form transition of C. albicans, and impaired capsule and melanin production of C. neoformans. Addition of 10 MIC paeonol to the medium did not shorten the lifespan of C. elegans, and 2 MIC paeonol could effectively protect the growth of C. albicans and C. neoformans-infected C. elegans. Furthermore, RNA sequencing was empolyed to examine the transcript profiling of C. albicans and C. neoformans biofilm cells in response to 1/2 MIC paeonol. RNA sequencing data revealed that paeonol treatment impaired biofilm formation and mature of C. albicans through presumably downregulating the expression level of initial filamentation, adhesion and growth-related gene as well as biofilm biosynthesis genes, while paeonol damaged biofilm formation and mature of C. neoformans through presumably upregulating the expression level of ergosterol biosynthesis-related genes. Together, the findings of this study indicates that paeonol can be explored for candidate antifungal agents for combating serious single and mixed infections caused by C. albicans and C. neoformans.